The role of forensic entomology in criminal investigation: its development and application in Malaysian administration of criminal justice / Raja Muhammad Zuha Raja Kamal Bashah - Raja Muhammad Zuha, Raja Kamal Bashah (2005)
Forensic entomology in criminal investigation has been considered as one of the most important aspect in criminal justice. As it stands as corroborative evidence in court, the importance of scientific method in forensic entomology reveal the structure of conviction towards the guilty party by estimating time of death, finding cause of death and ·· determine the location of a body. This paper discussed the importance of forensic entomological data in criminal investigation. It is revealed that such evidence just not only helps to establish post-mortem interval (PMI) but the role of the scientific nature of such evidence could provide facts to corroborate conviction or even overturn a conviction. It is also important to homogenize the methods of entomological evidence recovery in the field and in the laboratory as any defect could affect the expert testimony in court. The malpractice of evidence recovery could become the weaken factor for the evidence to be admissible in court. Several problematic factors identified from insect evidence recovery at the crime scene in Malaysia. However, ideas, how to strengthen the value of forensic entomological data is displayed through standard guidelines and procedures.